Housing satisfaction, homeownership and housing mobility: a panel data analysis for twelve EU countries - Luis Diaz-Serrano (Institute for the Study of Labor (IZA), 2006)
We investigate the determinants of housing satisfaction in twelve EU countries. To do so, we use panel data covering the period 1994-2001, which allows us to control for individual heterogeneity. We carry out separate estimates on the determinants of housing satisfaction for homeowners and for renters and observe that: i) the tenure status is critical in determining the level of housing satisfaction; ii) housing satisfaction acts as trigger event of housing mobility, and; iii) dissatisfied renters are more likely to move than their homeowners counterparts. Our results also allow us to conclude that self-reported housing satisfaction is a meaningful variable able to explain individual's objective economic behavior, since it is able to anticipate movements in the households' demand for housing
Keywords: 330